KESANTUNAN BERBAHASA INDONESIA DALAM TINDAK TUTUR ILOKUSI PARA DAI DI MESJID NURUSH SHIDDIQ KELURAHAN GUNUNG PANGILUN KECAMATAN PADANG UTARA - Yuliza Yuliza; Novia Juita; Ngusman Ngusman (Faculty of Languages and Arts, Universitas Negeri Padang, 2013)
This research was conducted to describe: (1) the types of speech acts ilokusi teen wird, (2) tells the strategy used in the speech act ilokusi at wirid adolescents, and (3) the context of the situation said in a speech act ilokusi at teen wird in mosque Nurush Siddiq Village Mount Pangilun Northern District of Padang, Padang. The data of this study is the speech act propagators in Nurush Siddiq mosque. The data source of this research is the language spoken in the dai teens wird Nurush Siddiq mosque Pangilun Mountain Village Northern District of Padang, Padang. Data obtained using recording techniques. Data obtained through recordings and classified based on the type of speech act ilokusi, recalled the strategy, tells of the context and linguistic politeness then interpreted and inferred. Based on these results, we can conclude that the activities teens wird Nurush Siddiq mosque Pangilun Padang District Mountain Village North is assertive speech acts, speech acts directive, expressive speech acts, speech acts and declarations. Strategies used tells Nurush Siddiq mosque preacher in the Village of Mount Pangilun Northern District of Padang, which directly tells the strategy with no strings attached, strings attached directly to the positive politeness, and strategy-spoken directly with strings attached negative politeness. Propagators in the context of the situation said in the speech act ilokusi Nurush Siddiq mosque Pangilun Mountain Village North Padang District said in a touchy situation relaxed atmosphere tends to use the strategy frankly recalled with strings attached positive politeness; said in a touchy situation likely to use a formal setting strategy frankly recalled with strings attached negative politeness; situation said the topic is not sensitive relaxed atmosphere tends to use the strategy frankly recalled with no strings attached; situation said the topic is not sensitive formal atmosphere tends to use the strategy frankly recalled with no strings attached.